Penerapan dan Evaluasi Promosi Gizi Pada Anak Sekolah di SD dan SMP Kota Yogyakarta - Budiningsari, Dwi; Hartriyanti, Yayuk; Hardiyanti, Marina; Witaningrum, Riani; Annisa Putie, Sridanti; Ryveka, Aurellia; Guna Risma, Aini; Nur Andani, Anisya (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Nutrition programs to overcome adolescent’s nutrition problems using a school-based approach are considered the most effective nutrition program strategy. As an effort to support nutrition programs at the school level, SEAMEO RECFON, together with experts in the field of health nutrition and strategic partners developed the "School Based Nutrition Promotion" module which was created for various targets including academics, policy makers, program implementers, school communities and the general public. This activity aims to implement a school-based nutrition promotion program as an effort to improve nutritional and health status and prevent degenerative diseases in children and adolescents. The method used is quasi-experimental research with a pre and post-test design without a control group design. The targets of this activity are teachers, principals and staff at Syuhada Mosque Elementary School and State Junior High School 2 Yogyakarta. Activities carried out include education and evaluation of the implementation of the SBNP module, student nutrition education, and training for health nutrition cadres. The result of this activity is that the average student score increases after being given education. The results of the assessment of the SBNP book were that the average elementary and junior high school teachers gave agree marks for all aspects, and for all aspects there was no significant difference between the average scores given by teachers except for aspect 4.